ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL (STUDI PADA PT. BANK MEGA, TBK) - Feriana Binti Rahmawati; Arisyahidin Arisyahidin; Eka Askafi (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to determine the level of bank’s health at PT. Bank Mega, Tbk seen from the risk profile, good corporate governance, earnings, and capital factors during the period of 2014 to 2018. The data analysis method in this study is a descriptive analysis with a quantitative approach. The results of data analysis can be explained that the bank’s health level at PT. Bank Mega, Tbk based of the risk profile factor shows that the majority of NPLs are predicated as healthy and LDR banks are considered to be very healthy. The good corporate governance factor shows the bank titled as good. The earning factor shows that the majority of bank ROA has a very healthy predicate and bank NIM has fluctuated from a healthy predicate to a very healthy predicate for three years and returned to healthy predicate in 2018. Capital factor shows a bank CAR is more than 12% which has a very healthy predicate. So the assessment of the level of bank’s health at PT. Bank Mega, Tbk seen from the risk profile, good corporate governance, earnings, and capital factors during the period of 2014-2018 included into the Very Healthy category.